If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5 = 2x + -11 Reorder the terms: 5 + 6x = 2x + -11 Reorder the terms: 5 + 6x = -11 + 2x Solving 5 + 6x = -11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + 6x + -2x = -11 + 2x + -2x Combine like terms: 6x + -2x = 4x 5 + 4x = -11 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + 4x = -11 + 0 5 + 4x = -11 Add '-5' to each side of the equation. 5 + -5 + 4x = -11 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = -11 + -5 4x = -11 + -5 Combine like terms: -11 + -5 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| t-19=-2(t+5) | | z-6=-10 | | v^2-20v+19=0 | | p-22=3(2p-4) | | 6x-5=2x-11 | | -4+a=15 | | 6x+7y=13 | | 12x+5=8x+13 | | 2y-6=9-3y | | w^2+6w=-3 | | log(y)=1.6 | | 4=m+19 | | 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 | | -x-2/7=x+1/6+4/7 | | 12x-18=10x+10 | | 5c-4b= | | 4n+1-5n=6n+7-9n | | 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 |